The investigation of sacroiliitis with different imaging techniques in spondyloarthropathies - ATAGÜNDÜZ, MEHMET PAMİR; DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2005)
Purpose: The aim of this study was to compare the value of different imaging techniques in spondyloarthropathy (SpA) patients with inflammatory low back pain. Patients and Methods: We evaluated 54 patients who fulfilled the European spondyloarthropathy classification criteria and had inflammatory low back pain. They were subdivided into two groups according to changes on plain radiography rated on a 0-4 scale according to modified New York criteria. Group A patients had at least grade-2 unilateral or bilateral changes in the sacroiliac (SI) joints, whereas group B included patients with radiologic changes not exceeding grade 0-1. Quantitative SI scintigraphy and magnetic resonance imaging (MRI) were performed to investigate the value of these techniques to the diagnosis of sacroiliitis, and the sacroiliac joint:sacrum uptake ratios were calculated. Scintiscanning was done in 80 healthy subjects to define the normal range. Results: The sensitivities of plain radiography, quantitative SI scintigraphy, and MRI were 61%, 55%, and 89%, respectively, among the patients with SpA. MRI and quantitative SI scintigraphy detected sacroiliitis in 97% and 49% of group A, respectively. In group B, these results were 76% and 66%, respectively. Conclusion: Magnetic resonance imaging is the most sensitive method for detecting acute or chronic changes in SpA patients with histories of inflammatory low back pain and normal or indeterminate findings on plain radiographs.
Keywords: magnetic resonance imaging; plain radiography; quantitative sacroiliac scintigraphy; sacroiliitis; spondyloarthropathies; ANKYLOSING-SPONDYLITIS; COMPUTED-TOMOGRAPHY; ACTIVE SACROILIITIS; SCINTIGRAPHY; DIAGNOSIS; RADIOGRAPHY; CRITERIA